Thermal fluctuations of (non)linearly charged BTZ black hole in massive gravity - Pourhassan, Behnam; Hendi, Seyed Hossein; Upadhyay, Sudhaker; Sakalli, Izzet; Saridakis, Emmanuel N. (World Scientific Publ Co Pte Ltd, 2023)
In this paper, we consider a charged BTZ black hole in asymptotically AdS spacetime of massive gravity to study the effect of the thermal fluctuations on the black hole thermodynamics. We consider the Einstein-Born-Infeld solution and investigate critical points and stability. We also compare the results with the case of Einstein-Maxwell solutions. Besides, we find that thermal fluctuations, which appear as a logarithmic term in the entropy, affect the stability of the black hole and change the phase transition point. Moreover, we study the geometrical thermodynamics and find that the behavior of the linear Maxwell solution is the same as the nonlinear one.
Keywords: Black hole; thermodynamics; thermal fluctuations; massive gravity